Management and Employee Control in Current Industrial Work - Holt, Helle; Hvid, Helge (Nordic Journal of Working Life Studies, 2014)
This article examines how employee control is affected by the ongoing erosion of boundaries in work organization and established boundaries in the relationship between employees and management. One assumption is that the erosion of boundaries offers potential for increased employee control, meaning increased autonomy or self-determination at work (employee control how and when to do what). This assumption is supported by theories on the psychosocial working environment. Another assumption is that the erosion of boundaries threatens the frontiers from where employees can defend their interests, and consequently reduces employees’ control of their work (what and how much to do). This assumption is supported by “labor process theory.” This article studies control and the erosion of boundaries in two case factories in the food industry. Two perspectives are applied: the psychosocial working environment and “labor process theory.”